Contribution of skeletal muscle and serum lipids to muscle contraction induced by neuromuscular electrical stimulation in older individuals. Issue 6 (21st March 2022) - Yoshiko, Akito; Maeda, Hisashi; Takahashi, Hideyuki; Koike, Teruhiko; Tanaka, Noriko; Akima, Hiroshi
Abstract: Intramyocellular lipids (IMCL) stored in droplets in muscle cells and free fatty acids (FFA) from fat cells in the blood are the main substrates of adenosine triphosphate during continuous muscle contractions of relatively lower intensity. Although it is known that the lipid oxidative capacity decreases with aging, the effect of IMCL and FFA on muscle contraction in older individuals remains unclear. The purpose of this study was to investigate the contribution of skeletal muscle lipids and blood lipids as energy sources for muscle contraction in older individuals. Eighteen older individuals (mean age: 70.4 ± 3.5 years) underwent muscle contraction intervention induced by intermittent neuromuscular electrical stimulation (NMES) to the vastus lateralis for 30 min. Fasting blood samples were obtained and proton magnetic resonance spectroscopy ( 1 H‐MRS) was performed before and after NMES, and the parameters (including IMCL and extramyocellular lipid [EMCL]) from 1 H‐MRS, along with FFA and adiponectin levels, were analyzed using the blood samples of all participants. Levels of IMCL and EMCL did not change ( p  > 0.05); however, FFA and adiponectin levels decreased from 1.1 ± 0.5 mEq/L to 0.8 ± 0.2 mEq/L and 12.0 ± 5.3 μg/ml to 11.4 ± 5.0 μg/ml, after NMES ( p  < 0.05), respectively. These findings indicate that serum lipids, but not skeletal muscle lipids, are the energy substrate utilized during involuntary muscle contraction in older individuals. Abstract : FFA significantly decreased after muscle contraction, although IMCL and EMCL did not change. These findings suggest that FFA were the energy source utilized during involuntary muscle contraction.